Diamine derivative of a ruthenium(II)-polypyridyl complex for chemodosimetric detection of nitrite ion in aqueous solution - Ghosh, Amrita; Das, Priyadip; Saha, Sukdeb; Banerjee, Tanmay; Bhatt, Harshad B.; Das, Amitava (Inorganica Chimica Acta, 2011)
Nitrite is quite an abundant anion in the environment. It, however, becomes toxic to human life, as well as aquatic animals when present above the permissible concentration level. We have reported here a Ru(II)-polypyridyl-based complex (1) for chemodosimetric detection of nitrite ion in aqueous solution. Formation of the new triazole based complex, generated by reaction of 1 and N2O3, is ascertained by comparing its properties with a presynthesised triazole complex.

Photoactive RuII-polypyridyl complexes that display sequence selectivity and high-affinity binding to duplex DNA through groove binding - Ghosh, Amrita; Das, Priyadip; Gill, Martin R.; Kar, Prasenjit; Walkar, Michael G.; Thomas, Jim A.; Das, Amitava (Chemistry A European Journal, 2011)
The duplex-DNA binding properties of a nonintercalating polypyridyl ruthenium(II) complex that incorporates a linear extended ligand with a catechol moiety has been probed with a variety of photo- and biophysical techniques. These studies reveal that the complex groove binds to DNA sequences biphasically, and displays binding constants equivalent to those of high-affinity metallointercalators. The complex also displays preferential binding to AT-rich sequences. Changes in the structure of the coordinated catechol ligand and the incorporation of intercalating ancillary ligands into the complex were found to modulate both the optical-binding response and binding parameters of the system, which indicates that the catechol moiety plays a crucial role in the observed enhancement to binding affinities.

Receptor design and extraction of inorganic fluoride ion from aqueous medium - Das, Priyadip; Mandal, Amal Kumar; Kesharwani, Manoj K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2011)
A receptor with acidic methylene hydrogens is found to act as an efficient binding mode for F−. This reagent could as well be used for selective and quantitative extraction of F− from the aqueous solution of NaF and sea water.

Urea/thiourea derivatives and Zn(II)-DPA complex as receptors for anionic recognition-a brief account - Das, Priyadip; Mahato, Prasenjit; Ghosh, Amrita; Mandal, Amal Kumar; Banerjee, Tanmay; Saha, Sukdeb; Das, Amitava (Journal of Chemical Sciences, 2011)
This review covers few examples of anion complexation chemistry, with a special focus on urea/thiourea-based receptors and Zn(II)-dipicolyl amine-based receptors. This article specially focuses on structural aspects of the receptors and the anions for obtaining the desire specificity along with an efficient receptor–anion interaction. Two types of receptors have been described in this brief account; first one being the strong hydrogen bond donor urea/thiourea derivatives, which binds the anionic analytes through hydrogen bonded interactions; while, the second type of receptors are coordination complexes, where the coordination of the anion to the metal centre. In both the cases the anion binding modulate the energy gap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) and thereby the spectroscopic response. Appropriate choice of the signalling unit may allow probing the anion binding phenomena through visual detection.

Zn(II) and Cd(II)-based complexes for probing the enzymatic hydrolysis of Na4P2O7 by alkaline phosphatase in physiological conditions - Das, Priyadip; Sourish, Bhattacharya; Sandhya, Mishra; Das, Amitava (Chemical Communications, 2011)
Newly synthesized Zn(II) and Cd(II)-based complexes show unique selectivity towards inorganic pyrophosphate (PPi) in 100% aqueous medium at pH = 7.4 and act as a "turn-on" and "turn-off" real-time assay, respectively, for the evaluation of the enzymatic activity of alkaline phosphatase.

ZnII-2,2?:6?,2?-terpyridine-based complex as fluorescent chemosensor for PPi, AMP and ADP - Das, Priyadip; Ghosh, Amrita; Kesharwani, Manoj K.; Ramu, Vadde; Ganguly, Bishwajit; Das, Amitava (Europian Journal of Inorganic Chemistry, 2011)
A new ZnII–2,2′:6′,2″-terpyridine complex, derivatized with a coumarin moiety (L1Zn), acts as a fluorescent chemosensor for different biologically important phosphates like PPi, AMP and ADP in mixed aqueous media. Depending on the proportion of the aqueous fraction present in the solvent mixture, L1Zn shows a preference for different phosphate moieties at physiological pH. In an aqueous acetonitrile (2:3, v/v) medium this reagent shows a preference for AMP as compared to ADP, ATP and PPi. The binding affinities of L1Zn with different phosphate ions and associated shifts in the electronic spectra were rationalized by DFT calculations. Such an example of a receptor that is selective for AMP under physiological conditions is rare in the literature.

Alternative approach: a highly selective dual responding fluoride sensor having active methylene group as binding site - Das, Priyadip; Kesharwani, Manoj K.; Mandal, Amal K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Org Biomol Chem., 2012)
A newly designed phosphonium derivative (L) having active methylene functionality, shows unusual preference towards F− over all other anions. The binding process through C–H⋯F− hydrogen bond formation was probed by monitoring the changes in either electronic or luminescence spectra. Changes in both cases are significant enough to allow visual detection. The loss of molecular flexibility of L on forming L·F− effectively interrupts the non-radiative deactivation pathway and accounts for the observed switch on fluorescence response. The results of the time-resolved emission studies for L and L·F− using a time-correlated single photon counting technique further corroborate this presumption. The excellent preference of L towards F− is attributed to an efficient hydrogen bonding interaction between the strongly polarized methylene protons and F−, which delineates the subtle difference in the affinity among other competing anionic analytes like CN−, H2PO4−, CH3CO2−, etc. The relative affinities of various anions and the preferential binding of F− to reagent L are also rationalized using computational studies.

Highly selective and dual responsive test paper sensor of Hg2+/ Cr3+ for naked eye detection in neutral water - Das, Priyadip; Ghosh, Amrita; Bhatt, Hitesh; Das, Amitava (RSC Advances, 2012)
A highly selective and sensitive colorimetric and fluorogenic sensor (L1) for Hg2+/Cr3+ is reported. This reagent (L1) was synthesized by reacting 4-((4 (dimethylamino)phenyl)diazenyl)benzene-1-sulfonyl chloride, which has a dimethylaminophenyldiazenyl fragment as a photoactive signalling unit, with 2,2′-(3,3′-azanediylbis(propane-3,1-diyl))diisoindoline-1,3-dione as the receptor fragment. The reagent was characterized by standard analytical and spectroscopic techniques. Electronic spectral studies revealed that the reagent was selective for Hg2+ and Cr3+ in the presence of all other metal ions of Group 1A, IIA and all other common transition metal ions. On binding of L1 to the Hg2+ or Cr3+ centres, a new intense absorption band with a λmax of 509 nm appeared with associated changes in the visually detectable solution colour from yellow to red. Fluorescence spectral studies revealed a significant enhancement in the emission intensities upon coordination to Hg2+ or Cr3+ without any change in the emission wavelength. This could be explained by the efficient interruption of the photo induced electron transfer signalling mechanism involving an unshared pair of electrons from the central tertiary amine centre. An easy to prepare paper test kit, which was obtained by soaking the filter paper in a dichloromethane solution of L1, presents an approach that could be successfully used in the detection of Hg2+ or Cr3+ ions present in neutral aqueous media. This indicates the potential application of this dip strip type sensor for the detection of Hg2+ and Cr3+ in neutral aqueous environments without any spectroscopic instrumentation. Importantly, this reagent binds specifically to Cr3+ in the presence of an excess of iodide ions, which act as a masking agent for Hg2+. To the best of our knowledge, there are very few examples of detection limits lower than the present test strip for Hg2+ in the literature, while, for Cr3+, no such report is available.

New chemodosimetric reagents as ratiometric probes for cysteine and homocysteine and possible detection in living cells and in blood plasma - Das, Priyadip; Mandal, Amal Kumar; Chandar, Nellore Bhanu; Baidya, Mithu; Bhatt, Harshad B.; Ganguly, Bishwajit; Ghosh, Sudip K.; Das, Amitava (Chemistry a European Journal, 2012)
In this work, we have rationally designed and synthesized two new reagents (L1 and L2), each bearing a pendant aldehyde functionality. This aldehyde group can take part in cyclization reactions with β- or γ-amino thiols to yield the corresponding thiazolidine and thiazinane derivatives, respectively. The intramolecular charge-transfer (ICT) bands of these thiazolidine and thiazinane derivatives are distinctly different from those of the molecular probes (L1 and L2). Such changes could serve as a potential platform for using L1 and L2 as new colorimetric/fluorogenic as well as ratiometric sensors for cysteine (Cys) and homocysteine (Hcy) under physiological conditions. Both reagents proved to be specific towards Cys and Hcy even in the presence of various amino acids, glucose, and DNA. Importantly, these two chemodosimetric reagents could be used for the quantitative detection of Cys present in blood plasma by using a pre-column HPLC technique. Such examples are not common in contemporary literature. MTT assay studies have revealed that these probes have low cytotoxicity. Confocal laser scanning micrographs of cells demonstrated that these probes could penetrate cell membranes and could be used to detect intracellular Cys/Hcy present within living cells. Thus, the results presented in this article not only demonstrate the efficiency and specificity of two ratiometric chemodosimeter molecules for the quantitative detection of Cys and Hcy, but also provide a strategy for developing reagents for analysis of these vital amino acids in biological samples.
Keywords: charge transfer; chemodosimetric detection; cysteine/ homocysteine sensors; fluorescent probes; imaging agents; ratiometric probes

Recognition of Hg2+ion through restricted imine isomerization: crystallographic evidence and imaging in live cells - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Suresh, E.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic Letters, 2012)
A newly synthesized imine-based receptor (L) showed remarkable specificity toward the Hg2+ ion in aqueous media over other metal ions. Coordination of L to Hg2+ induces a turn-on fluorescence response. This was explained based on the restricted imine isomerization along with PET on coordination to Hg2+. X-ray structural evidence tends to favor a C–C bond rotation rather than C═N isomerization for adopting a favorable conformation in L for coordination to Hg2+. This reagent could be used for imaging the accumulation of Hg2+ ions in HeLa cells.

Restricted conformational flexibility of a triphenylamine derivative on the formation of host-guest complexes with various macrocyclic hosts - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Das, Amitava (Chemistry a European Journal, 2012)
Herein, we report the host–guest-type complex formation between the host molecules cucurbit[7]uril (CB[7]), β-cyclodextrin (β-CD), and dibenzo[24]crown-8 ether (DB24C8) and a newly synthesized triphenylamine (TPA) derivative 1X3 as the guest component. The host–guest complex formation was studied in detail by using 1H NMR, 2D NOESY, UV/Vis fluorescence, and time-resolved emission spectroscopy. The chloride salt of the TPA derivative was used for recognition studies with CB[7] and β-CD in an aqueous medium. The restricted internal rotation of the guest molecule on complex formation with either of these two host molecules was reflected in the enhancement of the emission quantum yield and the average excited-state lifetime for the triphenylamine-based excited states. Studies with DB24C8 as the host molecule were performed in dichloromethane, a medium that maximizes the noncovalent interaction between the host and guest fragments. The Förster resonance energy transfer (FRET) process involving DB24C8 and 1(PF6)3, as the donor and acceptor fragments, respectively, was established by electrochemical, steady-state emission, and time-correlated single-photon counting studies.

Taco complex derived from a bis-crown ether capable of executing molecular logic operation through reversible complexation - Mandal, Amal Kumar; Das, Priyadip; Mahato, Prasenjit; Acharya, Suhash; Das, Amitava (Journal of Organic Chemistry, 2012)
As learned from natural systems, self-assembly and self-sorting help in interconnecting different molecular logic gates and thus achieve high-level logic functions. In this context, demonstration of important logic operations using changes in optical responses due to the formation of molecular assemblies is even more desirable for the construction of a molecular computer. Synthesis of an appropriate divalent as well as a luminescent crown ether based host 1 and paraquat derivatives, 2(PF6)2 and 3(PF6)2, as guests helped in demonstrating a reversible [3](taco complex) (1·{2(PF6)2}2 or 1·{3(PF6)2}2) formation in nonpolar solvent. Detailed 1H NMR studies revealed that two paraquat units were bound cooperatively by the two crown units in 1. Because of preorganization, the flexible host molecule 1 adopts a folded conformation, where each of two paraquat units remain sandwiched between the two aromatic units of each folded crown ether moiety in 1. Disassembly of the “taco” complex in the presence of KPF6 and reassembly on subsequent addition of DB18C6 was initially demonstrated by 1H NMR spectral studies, which were subsequently corroborated through luminescence spectral studies. Further, luminescence spectral responses as output signals with appropriate and two independent molecular inputs could be correlated to demonstrate basic logic operation like OR and YES gates, while the results of the three molecular inputs could be utilized to demonstrate important logic operation like an INHIBIT gate.

CN? specific turn-on phosphorescent probe with probable application for enzymatic assay and as an imaging reagent - Reddy, Upendar G.; Das, Priyadip; Saha, Sukdeb; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2013)
A new “turn-on” luminescence probe for imaging the uptake of 0.2 ppm inorganic CN− in live HeLa cells as well as for probing the CN− generation through an enzymatic process in a virtual aqueous medium at appropriate pH.

Designing a thiol specific fluorescent probe for possible use as a reagent for intracellular detection and estimation in blood serum: kinetic analysis to probe the role of intramolecular hydrogen bonding - Das, Priyadip; Mandal, Amal Kumar; Reddy, Upendar G.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic & Biomolecular Chemistry, 2013)
A new and simple chemodosimetric probe L-1 is utilized for the selective detection of biothiols in the presence of other relevant amino acids under physiological conditions (pH = 7.4). This eventually led to a turn-off luminescence response due to an effective photoinduced electron transfer based signaling mechanism. A comparison of the results of the fluorescence kinetic analysis and H-1 NMR studies of the reaction between thiol and L-1 or the analogous compound L-2 revealed the role of intramolecular hydrogen bonding in activating the imine functionality towards nucleophilic addition. Such an example is not common in contemporary literature. Conventional MTT assay studies revealed that this probe (L-1) has low cytotoxicity. Results of the cell imaging studies revealed that this probe was cell membrane permeable and could detect the intracellular distribution of biothiols within living HeLa cells. Furthermore, our studies with human blood plasma demonstrated the possibility of using this reagent for the quantitative optical detection of total biothiols in biological fluid. Such an example for the detection of biothiols in real biological samples is rare in the contemporary literature. These results clearly demonstrate the possibility of using this reagent in medicinal biology and diagnostic applications.

Role of metal ion in specific recognition of pyrophosphate ion under physiological conditions and hydrolysis of the phosphoester linkage by alkaline phosphatase - Das, Priyadip; Chandar, Nellore Bhanu; Chourey, Shishir; Agarwalla, Hridesh; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2013)
Complexes synthesized from Zn(II), Cu(II), and Cd(II), using a dipicolyl amine derivative (L), showed unique specificity toward pyrophosphate ion (PPi or P4O74-) among all other common anionic analytes, including different biologically significant phosphate ion (PO43-, H2PO42-) or phosphate-ion-based nucleotides, such as AMP, ADP, ATP, and CTP. However, the relative affinities of PPi toward these three metal complexes were found to vary and follow the order K-a(L.Zn-PPi) > are given in units of (L.Cu-PPi)(a) >= K-a(L.Cd-PPi). Luminescence responses of the receptor L were substantial on binding to Zn2+ and Cd2+, while relatively a much smaller luminescence response was observed in the presence of Cu2+. Luminescence responses of L.M-PPi (M is Zn2+, Cd2+, and Cu2+) were further modified on binding to the PPi ion. This could be utilized for quantitative detection of PPi in physiological condition as well as for developing a real time ``turn-on'' (for L.Zn and L.Cu) and ``turn-off'' (for L.Cd) fluorescence assay for evaluating the enzymatic activity of alkaline phosphatase (ALP). Experimental results revealed how the subtle differences in the binding affinities between PPi and M in L.M (M is Zn2+, Cd2+, and Cu2+), could influence the cleavage of the phosphoester linkage in PPi by ALP. The DFT calculations further revealed that the hydrolytic cleavage of the metal ion coordinated phosphoester bond is kinetically faster than that for free PPi and thus, rationalized the observed difference in the cleavage of the phosphoester bond by an important mammalian enzyme such as ALP in the presence of different metal complexes.

Overview of the recent developments on Hg2+ recognition - Mahato, Prasenjit; Saha, Sukdeb; Das, Priyadip; Agarwalla, Hridesh; Das, Amitava (RSC Advances, 2014)
Adverse influences of mercury on living organisms are well known. Despite efforts from various regulatory agencies, the build-up of Hg2+ concentration in the environment is of serious concern. This necessitates the search for new and efficient reagents for recognition and detection of Hg2+ in environmental samples as well as for application in diagnostics. Among various detection processes adopted for designing such reagents, generally methodologies that allow associated changes in spectra properties are preferred for the obvious ease in the detection process. Significant changes in the electronic spectral pattern in the visible region of the spectrum also induce detectable changes in solution colour for naked-eye detection and are useful for developing reagents for in-field sample analysis with yes-no type binary responses. However, reagents that allow detection of Hg2+ with associated fluorescence on response are useful for detection of Hg2+ in environmental samples, as well as for use as an imaging reagent, for detection of cellular uptake. High spin-orbit coupling constant for Hg2+ along with its high solvation energy in aqueous medium poses a challenge in developing efficient reagents with fluorescence on response that work in aqueous medium/physiological condition. To get around this problem, several methodologies, like conversion of rhodamine derivative spirolactam to strongly fluorescent xanthenes that form on binding to Hg2+, chemodosimetric reaction for generation of a new luminescent derivative, have been adopted. Apart from these, modified charge transfer processes on binding to Hg2+ have also been utilized for designing reagents for optical detection of Hg2+. Immobilization of such reagents on solid surfaces also led to the development of self-indicating Hg2+ ion scavengers. All such examples are discussed in the present review.

Structure-property correlation of halogen substituted benzothiazole crystals - Thekkeppat, Nipun P.; Singla, Labhini; Tothadi, Srinu; Das, Priyadip; Choudhury, Angshuman Roy; Ghosh, Soumyajit (Journal of Molecular Structure, 2021)
We have synthesized 3 benzothiazole crystals (1-3) based on existing knowledge of combining flexibility and optical properties towards achieving applications for flexible optoelectronics. However, one crystal was found to be elastically bendable and was found to comply necessary packing features for elasticity. Other two crystals do not obey packing features for elasticity hence they are brittle in nature. Further, Hirshfeld analysis illustrates that elastic crystal 1 possess more number of weak and dispersive interactions compared to other crystals. These interactions were instrumental in invoking elasticity. Moreover, crystals 1-3 were found to be fluorescent as well at specific excitation wavelengths. Therefore, among these crystals, particularly crystal 1 is considered as more promising candidate for flexible optoelectronics. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Benzothiazole crystals; Elasticity; Halogen bond; mechanical properties